Analysis of different training load monitoring methods in youth women handball players - Maciel, F. O.; Miranda, R.; Ferreira-Júnior, J. B.; Goulart, T.; Brandao, F.; Werneck, F. Z.; Bara-Filho, M. G. (Apunts Sports Medicine, 2022)
This study examined the association between different methods for training load (TL) monitoring during youth handball training. Distance covered, heart rate and session rating of perceived exertion [SRPE] were recorded during 12 training sessions in 14 youth women handball athletes (16.9±1.1 years). Internal load models based on SRPE and Edwards` Trimp were calculated. An oscillatory feature was observed for the three methods of TL assessment (SRPE: 383±159 A.U., Edwards` Trimp: 252±71 A.U., total distance: 3997±1291 m). A large correlation was found between Edwards` Trimp and distance covered (r=0.59). A moderate correlation was observed for Edwards` Trimp vs. SRPE (r=0.36), and between SRPE vs. distance covered (r=0.49). Shared variances of 13-35% were observed between TL methods comparisons. The results suggest that different constructs seem to be measured by each load model. Additionally, SRPE is a simple and low-cost method that might be used for TL monitoring in handball.